Drug design and discovery in Alzheimer's disease - Rahman, Atta-ur-, 1942-; Choudhary, Muhammad Iqbal (Elsevier, 2014)
Drug Design and Discovery in Alzheimer's Disease includes expert reviews of recent developments in Alzheimer's disease (AD) and neurodegenerative disease research. Originally published by Bentham as Frontiers in Drug Design and Discovery, Volume 6and now distributed by Elsevier, this compilation of the sixteen articles, written by leading global researchers, focuses on key developments in the understanding of the disease at molecular levels, identification and validation of molecular targets, as well as innovative approaches towards drug discovery, development, and delivery. Beginning with an.